Chronic osteomyelitis risk is associated with NLRP3 gene rs10754558 polymorphism in a Chinese Han Population - Yu-dun Qu; Nan Jiang; Jia-xuan Li; Wei Zhang; Chang-liang Xia; Shuan-ji Ou; Yang Yang; Yun-fei Ma; Yong Qi; Chang-peng Xu (BMC, 2024)
Abstract Background Single nucleotide polymorphisms (SNPs) in the nucleotide-binding domain leucine-rich repeat protein-3 (NLRP3) gene are reported to be linked to many inflammatory disorders. However, uncertainty persists over the associations between these SNPs and susceptibilities to chronic osteomyelitis (COM). This study aimed to investigate potential relationships between NLRP3 gene SNPs and the risks of developing COM in a Chinese Han cohort. Methods The four tag SNPs of the NLRP3 gene were genotyped in a total of 428 COM patients and 368 healthy controlsusing the SNapShot technique. The genotype distribution, mutant allele frequency, and the four genetic models (dominant, recessive, homozygous, and heterozygous) of the four SNPs were compared between the two groups. Results A significant association was found between rs10754558 polymorphism and the probability of COM occurence by the heterozygous model (P = 0.037, odds ratio [OR] = 1.541, 95% confidence interval [CI] = 1.025-2.319), indicating that rs10754558 may be associated with a higher risk of developing COM.In addition, possible relationship was found between rs7525979 polymorphism and the risk of COM development by the outcomes of homozygous (P = 0.073, OR = 0.453, 95% CI = 0.187-1.097) and recessive (P = 0.093, OR = 0.478, 95% CI = 0.198-1.151) models, though no statistical differences were obtained. Conclusions Outcomes of the present study showed, for the first time, that rs10754558 polymorphism of the NLRP3 gene may increase the risk of COM development in this Chinese Han population, with genotype CG as a risk factor. Nonetheless, this conclusion requires verification from further studies with a larger sample size.